Pengaruh Model Integratif Berdasarkan Daniel 6:1-28 Dalam Meningkatkan Pembelajaran Siswa di SDN Cibojong - Aris Antonius; Maria Titik Windarti (Jurnal Silih Asah, 2024)
Integrative learning is a study that contains more than one subject into a particular learning theme, so that it can provide students with experience in the learning process by using a field of study approach. The integrative learning process can be seen in aspects such as the time aspect and learning process, curriculum aspects and teaching aspects. Based on the results of observations that have been made, students' motivation and interest in learning is low. This is shown by students' lack of enthusiasm in participating in learning due to monotonous learning, teachers still using a dictation system and the provision of learning tools being inadequate so that the learning process feels saturated and boring. Therefore, the activity of implementing this integrative learning model requires students to be more active than the teacher who is the guide in the learning process. As for the steps that must be taken in this learning activity, students must interact with the learning material and must interact with learning resources so that they can easily master the concepts and indices in the integrative learning process.